FRI0118 Dekavil (F8IL10) – update on the results of clinical trials investigating the immunocytokine in patients with rheumatoid arthritis. (12th June 2018) - Galeazzi, M.; Sebastiani, G.; Voll, R.; Viapiana, O.; Dudler, J.; Zufferey, P.; Selvi, E.; Finzel, S.; Bootz, F.S.; Neri, D.; ,
Abstract : Background: The targeted pharmacodelivery of cytokines by means of antibody-fusion proteins aims at selective accumulation of the active compound at the site of disease while sparing healthy tissues. Dekavil (F8IL10) is a fully human fusion protein composed of the vascular targeting antibody F8 fused to the cytokine interleukin-10. A phase 1 dose escalation study in patients with rheumatoid arthritis (RA) has recently been completed. Dekavil is currently under investigation in a phase 2 clinical study for the treatment of RA. Objectives: The phase 1 study investigated safety, tolerability and the maximum tolerated dose of Dekavil when administered in combination with methotrexate (MTX). The currently ongoing phase 2 (in patients with active RA despite MTX therapy who had failed anti-TNF treatment) measures the mean change from baseline in DAS28-CRP between F8IL10 and placebo arms as primary endpoint. Methods: The target population of both RA studies comprises patients with active RA despite MTX therapy who had failed anti-TNF treatment. Dekavil is administered once weekly for 8 consecutive weeks by s.c. injection in combination with a fixed dose of MTX (10–25 mg). The recently completed phase 1 study investigated escalating doses of Dekavil (6–600 µg/kg +MTX). The ongoing randomised multicenter, double-blind, placebo-controlled phase 2 trial assesses therapeutic activity in two treatment groups (Dekavil 30 or 160 µg/kg plus MTX) and one placebo group (placebo plus MTX). Results: Dekavil was well tolerated up to the highest investigated dose (600 µg/kg) and an MTD was not reached. In 34 out of 35 patients treated in the phase 1 study no SAEs and no SUSARs were reported. One subject (cohort 9, 450 µg/kg) experienced a DLT (G2 purpura), which was accompanied by an SAE (G2 dyspnea, not drug related). The patient fully recovered within one week following corticosteroid administration. The most frequently observed adverse event was mild (G1) injection site reaction and occurred in 60% of the patients. Furthermore, two cases of drug related anaemia (G3 and G2; 160 µg/kg and 450 µg/kg, respectively) were reported in this study. All adverse reactions resolved completely. After 4 cycles of treatment, 36.4% of patients (12/33) exhibited ACR responses. The fraction of responses increased to 45.8% (11/24) after 8 cycles. Two patients achievedan ACR70 for more than 12 months after the last drug administration. As of January 2018, 25 patients have been treated in the phase 2 clinical study and neither SUSARs nor treatment-related deaths were recorded. Immunogenicity assessment is completed for the first 20 study subjects did not reveal an antibody response specific to F8IL10. An interim read-out after 45 patients will provide a more thorough understanding of the therapeutic activity of F8IL10. Conclusions: The data obtained in the population studied to date suggest that Dekavil may be a safe and well tolerated novel therapeutic for the potential treatment of RA. Disclosure of Interest: M. Galeazzi: None declared, G. Sebastiani: None declared, R. Voll: None declared, O. Viapiana: None declared, J. Dudler: None declared, P. Zufferey: None declared, E. Selvi: None declared, S. Finzel: None declared, F. Bootz Employee of: Philogen Group (Sponsor of the study), D. Neri Shareholder of: Philogen Group (Sponsor of the study)